Profile of Mutation on Drug Resistance Mycobacterium leprae Isolates in Indonesia Collected During 2003-2011 - RATNA WAHYUNI; DINAR ADRIATY; ISWAHYUDI ISWAHYUDI; CITA ROSITA SIGIT PRAKOESWA; INDROPO AGUSNI; SHINZO IZUMI (Microbiology Indonesia, 2012)
Multidrug therapy (MDT) regiment has been used for leprosy all over the world for more than 20 years. Drug resistances of Mycobacterium have been reported from many areas. The resistance mostly occurred due to mutation on the gene coding protein targeted by anti-leprosy drugs. Two hundreds and seventy M. leprae isolates from some area in Indonesia were examined for studying the profile of mutation among isolates collected during 2003-2011. Drug resistance determining region of the folP1 gene and the rpoB gene was sequenced. The results showed 5 isolates of M. leprae harboured mutation only in the folP1 gene and another isolate harbored mutation in both the folP1 and rpoB gene. The point mutation in the folP1 gene that was found in 2 isolates occurred in codon 53 (ACC→GCC; Thr→Ala). Double point mutations on codon 53 that was found in two isolates were ACC→AGA (Thr→Arg) and ACC→AGG (Thr→Arg). The point mutation in the folP1 geneoccurred in codon 55 were found in two isolates were CCC→CTC (Pro→Leu) and CCC→CGC (Pro→Arg). Whereas mutation in the rpoB gene in one isolate occurred in codon 410 was GAT→TAT (Asp→Tyr). These mutations that altered the amino acids of the protein revealed that isolates of M. leprae were resistant to drug with variable profiles